Teaching of Reference Service - Rahman, Abdul (Journal of Information and Knowledge, 1966)
Explains the duties and qualities of a reference librarian and indicates the content of a course in reference service. Describes the techniques for teaching reference service such as, 1 Clinical Method, 2 Discussion Method, 3 Preparatory work with reference books, 4 Find-me-out Method, 5 Practical or Workshop Method, and 6 Lecture Method. Describes with illustration the Case-Study Method of teahing reference service recently developed, and evaluates it. Gives a proforma for studying reference materials.